INFLUENCE OF LONG TERM FERTILIZATION ON YIELD AND ACTIVE POOLS OF SOIL ORGANIC CARBON IN RICE - RICE CROPPING SEQUENCE OF ONATTUKARA - G. KAVYASREE and V. MINI, (The Journal of Research ANGRAU, 2022)
The effect of long term fertilization on yield and active pools of soil organic carbon under ricericecropping sequence was studied during 2020-21 in a long term fertilization experiment conductedsince 1964 at Onattukara Regional Agricultural Research Station, Kayamkulam, Kerala. The resultsindicated that the application of FYM along with NPK fertilizers(80 kg N ha-1, 20 kg as FYM and 60 kgas A.S. + 40 kg P2O5 ha-1 as Rajphos + 40 kg K2O ha-1) as MOP resulted in significant increase in riceyield. Soil organic carbon, soil microbial biomass carbon, nitrogen, and phosphorus, water solublecarbon, water soluble carbohydrates and dehydrogenase activity were the highest under treatmentreceiving combined application of FYM and NPK fertilizers. These fractions contribute to the activepool of soil organic carbon and can be identified as an indicator of soil quality. Present study thusprovided an insight on how management practices affect crop yield and active pools of carbon.